2002
DOI: 10.1177/039139880202501015
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human Liver Cells as Source for Modular Extracorporeal Liver Support - a Preliminary Report

Abstract: Cell-based extracorporeal liver support is an option to assist or replace the failing organ until regeneration or until transplantation can be performed. The use of porcine cells or tumor cell lines is controversial. Primary human liver cells, obtained from explanted organs found to be unsuitable for transplantation, are a desirable cell source as they perform human metabolism and regulation. The Modular Extracorporeal Liver Support (MELS) concept combines different extracorporeal therapy units, tailored to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 11 publications
0
44
0
3
Order By: Relevance
“…Конструкция этого аппарата содержит биореактор, в котором афферентная жидкость перфузируется от центра к периферии, проходя через гепатоциты свиней (200-230 г), расположенные на полиэфирной матрице в специальном отсеке между двух слоев полиэфирных пластин [124]. Результаты I фазы клинических испытаний на семи пациентах с острой ПН показали улучшение неврологической симптоматики, снижение уровня аммиака и билирубина, отсутствие осложнений.…”
Section: аппарат Rfb (Radial-flow Bioreactor)unclassified
“…Конструкция этого аппарата содержит биореактор, в котором афферентная жидкость перфузируется от центра к периферии, проходя через гепатоциты свиней (200-230 г), расположенные на полиэфирной матрице в специальном отсеке между двух слоев полиэфирных пластин [124]. Результаты I фазы клинических испытаний на семи пациентах с острой ПН показали улучшение неврологической симптоматики, снижение уровня аммиака и билирубина, отсутствие осложнений.…”
Section: аппарат Rfb (Radial-flow Bioreactor)unclassified
“…Human hepatocytes are difficult to replicate in vitro, and daughter cells have not been shown to express sufficient levels of liver-specific functions [4,5]. One alternative is to use hepatocytes from other species.…”
Section: Cell Sourcesmentioning
confidence: 99%
“…Sauer et al (14) reported their experience with a bioartificial liver device characterized by seeding and long-term cultivation of human hepatocytes immediately after isolation. That device is maintained viable for 21 days by continuous replacement and supplementation of cell culture media and could be used for clinical treatment if requested thereafter it should be discarded due to loss of function.…”
Section: Case Reportmentioning
confidence: 99%